Kinerja Dinas Perhubungan manado dalam mengatasi kemacetan di Kota Manado - Losa, Calvin; Lengkong, florence Daicy; Ruru, Joorie (Sam Ratulangi University, 2015)
Abstract: The purpose of this research is to know the performance of the Department of transportation thecity of manado in overcoming bottlenecks in the city of manado. Congestion is the enemy of all citiesevolve how not everyone wants to be on time but sometimes we take advantage of the drive can be thecause of our loss. Department of transportation's been doing a lot of Manado City efforts in tacklingbottlenecks that occur one by working closely with the traffic police authorities in response to wildparking, but that's all it was only one of countless causes of congestion, the Department of transportationcurrently Manado alone must be firmer or more increase their performance so that later on the level ofcongestion in the town of manado alone can be cut down.In the research uses qualitative research methods type or descriptive. As for the variety of data (theinformant) in this research taken from the elements involved in the problem in thorough, namely: head ofDepartment of Transportation Department Secretary, Manado, the head of Road Freight traffic, head ofsystems development of transportation and road users (community). With the techniques of primary andsecondary data collection is done with the interview, observation and documentation study.The overall performance of the transport service of the city of manado in dealing with congestion inmanado city seen from the implementation of function-function which in size with the performancemeasurement indicators are pointed out by Dwiyanto 1995 (productivity, Responsiveness, quality ofservice, corporate responsibility and accountability) is still not optimal. It is proven congestion problems inthe city of manado in the handle well yet and Max.The Department of transport improves performance of Manado city in addressing bottlenecks in the workprogram for effectiveness suggest that will be made by the Department of transportation should be moreManado city in advance to be able to cope with problems on the streets of the city of Manado, for example:make regulations for vehicle ownership rights over 6 – 7 years in destroyed or recycled to reducebottlenecks and making the Road overpass. Quality of service in the Department of transportation in ordernot to complicate the community with conditions that are not important and of persons – the person whomade it more difficult to be in the stands. Response from the Department of transportation by takingaction against the congestion often occurs in Manado city must faster and creating pos – post on point – apoint of congestion in order to control the streets of the city of Manado. Department of transportation inthe future to further improve its velocity in response to things – things that exist in the streets of the city ofmanado, for example: reduction of public transport vehicles that are already not worth sharing andmaking the place/guard post in Manado city street setKey words: Department of transportation Performance of manado in overcoming bottlenecks